FAKTOR-FAKTOR YANG MEMPENGARUHI EFISIENSI BANK SERTA PENGUKURANNYA (STUDI PADA BPD GO PUBLIC DAN NON GO PUBLIC 2011-2019) - Hana Aulia Parasari (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2019)
The purpose of this studi are to measure the level of efficiency of regional development banks going public and non-going public in Indonesia in the period 2011-2019. In addition, it is also to identify what factors influence the level of efficiency of regional development banks going public and non-going public in Indonesia in the period 2011-2019. The method used in this study consists of 2 methods: for analyzing bank efficiency measurements using the non-parametric Data Envelopment Analysis (DEA) method and analyzing the factors that affect efficiency using the panel data regression model. The results of this study indicate that the efficiency level of 5 regional development banks going public and non-going public in Indonesia for the period of 2011- 2019 there are several banks that have fluctuating efficiency scores, but in carrying out their operations the BPD efficiency values show efficient and very efficient scores.Keywords: Bank Efficiency, Data Envelopment Analysis (DEA), regional development banks (BPD